Naming Chinese Dishes in a Cognitive Semantic Perspective - Monika Herliana; Saifus Somad; Rizki Utami (International Journal of Chinese Interdisciplinary Studies, 2025)
Naming Chinese dishes is a linguistic practice that not only reflects culinary aspects but also contains cognitive meanings related to society's culture, history, and social values ​​. This article examines Chinese dish naming from a cognitive linguistics perspective, focusing on how language patterns create associations, symbolism, and representation in the choice of food names. The documentary video A Bite of China (舌尖上的中国 Shéjiān Shàng de Zhōngguó) is a documentary video that documents various kinds of dishes throughout China. Documentation takes the form of broadcasts about the origins of the dish as well as the history and culture of the dish. The author analyzes how cognitive concepts, such as metaphors and conceptual schemes, influence how society chooses and understands dish names. The study results show that naming Chinese dishes contains cognitive semantic meaning. In his analysis, the name functions as culinary identification and an imaging concept originating from the source and target domains to convey cultural narratives, symbolism, and specific values ​​that are important in social life. By understanding this nomenclature, we can better appreciate the complexity of the interactions between language, culture, and cognition in constructing food meaning in Chinese culture.